2017
DOI: 10.1108/jsfe-01-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Timber under real fire conditions – the influence of oxygen content and gas velocity on the charring behavior

Abstract: (2017) "Timber under real fire conditions -the influence of oxygen content and gas velocity on the charring behavior", Journal of Structural Fire Engineering, https://doi.org/10.1108/JSFE-01-2017-0013 Permanent link to this document: https://doi.org/10.1108/JSFE-01-2017-0013 For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 5 publications
1
13
0
1
Order By: Relevance
“…As the timber is completely turned into char at approximately 300°C, the predicted temperature profile in the timber throughout the duration of the fire can be used to estimate the charring rate. Schmid et al (2016) showed that there is a practically constant ratio between charring rate and heat release rate. This ratio is used to determine the heat release rate of CLT from the calculated charring rates.…”
Section: Postflash Design Fires For Compartments With Exposed Timbermentioning
confidence: 99%
“…As the timber is completely turned into char at approximately 300°C, the predicted temperature profile in the timber throughout the duration of the fire can be used to estimate the charring rate. Schmid et al (2016) showed that there is a practically constant ratio between charring rate and heat release rate. This ratio is used to determine the heat release rate of CLT from the calculated charring rates.…”
Section: Postflash Design Fires For Compartments With Exposed Timbermentioning
confidence: 99%
“…Bei ausreichend großer Brennstoffmenge, i. d. R. Mobiliar, stellt sich in diesen Bränden im Raum ein sehr niedriger Sauerstoffgehalt ein. Dies ist ein Grund, warum es für Brandversuche jeder Art und insbesondere für brennbare Bauteile wie Brettsperrholz notwendig ist, den Sauerstoffgehalt zu dokumentieren, um die richtigen Schlussfolgerungen ziehen zu können .…”
Section: Brandprüfungenunclassified
“…Brandon [4] based his concept on a comparison of the heat release rate (HRR) measured in a large series of compartment experiments. The basis of the comparison by Brandon [4] was the HRR of cone calorimeter tests with timber specimens, where also the charring rate was measured [9,10]. Comparing the measured HRR and the charring rates observed in the compartment experiments, a significant difference between the estimated and the measured HRR was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Following Wade's methodology, a parameter study would be required between the bounds while Brandon's approach is stated to be conservative for the evaluated compartment experiments. Yet, as the significant reduction of the structural fuel was not apparent, the approach using a fitting factor was further studied by Schmid et al [10]. Schmid et al analysed the char layer with respect to its yield profile and the corresponding heat content.…”
Section: Introductionmentioning
confidence: 99%